2019
DOI: 10.3390/ijms20246225
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Generation of Oocytes from Ovarian Stem Cells (OSCs): In Search of Major Evidence

Abstract: The existence of ovarian stem cells (OSCs) in women as well as their physiological role in post-menopausal age are disputed. However, accumulating evidence demonstrated that, besides the animal models including primarily mice, even in adult women putative OSCs obtained from ovarian cortex are capable to differentiate in vitro into oocyte-like cells (OLCs) expressing molecular markers typical of terminal stage of oogonial cell lineage. Recent studies describe that, similarly to mature oocytes, the OSC-derived O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
1
21
0
1
Order By: Relevance
“…The lack of SCP3 expression in the cells was observed, which probably indicated the immaturity of these cells (Virant-Klun et al, 2008). Researchers also showed, by dividing OLCs into groups featuring large or small cells that SCP3 expressed only in large cells (Silvestris et al, 2019). The results of the present study also showed higher levels of expression of this gene in the second week in the group treated with melatonin 10 -7 M, which was a significant increase compared to the first week and controls.…”
Section: Discussionsupporting
confidence: 63%
“…The lack of SCP3 expression in the cells was observed, which probably indicated the immaturity of these cells (Virant-Klun et al, 2008). Researchers also showed, by dividing OLCs into groups featuring large or small cells that SCP3 expressed only in large cells (Silvestris et al, 2019). The results of the present study also showed higher levels of expression of this gene in the second week in the group treated with melatonin 10 -7 M, which was a significant increase compared to the first week and controls.…”
Section: Discussionsupporting
confidence: 63%
“…[ 13 , 42 ] Similarly, the literature reports that AMH dosage and a pre-treatment fertility evaluation can help in the identification of patients with deficient ovarian reserve and who could benefit from a fertility preservation technique. [ 43 ] In this study, there was a very small percentage of pregnancy failure: 1 had SAB and 1 had IVP; these percentages are typically reported in a general population [ 44 ] ; therefore, it is difficult to demonstrate a relationship. [ 45 ] The literature on the possible dangerous effects of cancer treatments on pregnancy did not show an increased risk of genetic or other defects in births of women previously receiving antineoplastic treatment.…”
Section: Discussionmentioning
confidence: 91%
“…The fertilization of stem cell-derived oocytes provides a new direction in the field of artificial reproductive techniques, which may be applied in the near future. Stem cells may be implanted in the patient's ovary or cultured into oocytes for in vitro fertilization [33][34][35].…”
Section: Identification and Isolation Of Ovarian Stem Cellmentioning
confidence: 99%
“…Furthermore, the epigenetic status of embryogenesis in postnatal mammalian gonads needs to be investigated [38]. With more research, the isolation of ovarian stem cells might become useful to increase the outcomes of ovarian tissue cryopreservation and transplantation [35,39,40].…”
Section: Identification and Isolation Of Ovarian Stem Cellmentioning
confidence: 99%